A Qualitative Investigation of Clients, Significant Others, and Clinicians’ Experiences of Using Wireless Microphone Systems to Manage Hearing Impairment - Nerina Scarinci; Mansoureh Nickbakht; Barbra H. Timmer; Katie Ekberg; Bonnie Cheng; Louise Hickson (Audiology Research, 2022)
This study aimed to explore the perceptions and experiences of adults with hearing impairment (HI), their significant others (SOs), and clinicians regarding the use and provision of wireless microphone systems (WMS). A qualitative descriptive methodology was used, with a total of 43 participants across three groups: (1) 23 adults with HI who used WMS; (2) 7 SOs of adults who used WMS; and (3) 13 clinicians who provided WMSs to adults with HI. Participants completed an individual semi-structured in-depth interview to explore their experiences, with the data analysed using thematic analysis. The analysis revealed five themes encompassing the perceptions and experiences of WMSs: (1) with experience and clear expectations, users believe that WMS can make a difference; (2) the trial and decision-making process is important; (3) clients’ experiences using WMS; (4) issues with WMS and technology; and (5) users require ongoing training and support to use WMS. These findings highlight the complexities of providing and using WMS with adults with HI. However, clients, SOs, and clinicians all reported that, with appropriate experience, expectations, training, and support, WMS can make a real difference in listening and communicating in different situations. There is also an opportunity to involve SOs more throughout the rehabilitation process.